Sistem Informasi Sentralisasi Keuangan Mingguan (Studi Kasus : GMIM Anugerah Koka, Kecamatan Tombulu) - Adelin Nelsyia Pieter; Marline Sofiana Paendong; Stephano Caesar Wenston Ngangi (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2023)
The procedure applied to the management of weekly financial data at GMIM Anugerah Koka, Tombulu District begins with the inclusion of financial funds from the congregation, BIPRA, Column, BIPRA coloumn, Elderly to the Treasurer of the Congregation and also the management of financial data at GMIM Anugerah Koka is still done manually and when calculating data finance still uses a calculator tool. With the development of technology so that a website-base weekly centralized financial information system can be carried out. The purpose of building this website-based weekly financial centralization information system is to make it easier for the Congregational Treasurer to manage weekly finances. The system was built and developed using the waterfall method starting from analysis, design, coding or implematation, testing, operation and maintenance. This weekly financial centralization website has two entities, namely the Treasurer as a manager who can login, input, edit, delete, view, print weekly financial data while MPJ can process weekly login, view, and print financial data.